Ribosome Assembly as Antimicrobial Target - Rainer Nikolay; Sabine Schmidt; Renate Schlömer; Elke Deuerling; Knud H. Nierhaus (MDPI AG, 2016)
Many antibiotics target the ribosome and interfere with its translation cycle. Since translation is the source of all cellular proteins including ribosomal proteins, protein synthesis and ribosome assembly are interdependent. As a consequence, the activity of translation inhibitors might indirectly cause defective ribosome assembly. Due to the difficulty in distinguishing between direct and indirect effects, and because assembly is probably a target in its own right, concepts are needed to identify small molecules that directly inhibit ribosome assembly. Here, we summarize the basic facts of ribosome targeting antibiotics. Furthermore, we present an in vivo screening strategy that focuses on ribosome assembly by a direct fluorescence based read-out that aims to identify and characterize small molecules acting as primary assembly inhibitors.